Redemption of the “spoiled identity:” the role of HIV-positive individuals in HIV care cascade interventions - Camlin, Carol S.; Geng, Elvin; Semitala, Fred; Wallenta, Jeanna; Kampiire, Leatitia; Bukusi, Elizabeth A.; Kwarisiima, Dalsone; Clark, Tamara D.; Kamya, Moses R.; Havlir, Diane V. (Journal of the International AIDS Society, 2017)
The concept of “therapeutic citizenship” has drawn attention to ways in which public testimony, the “story-telling in the public sphere” undertaken by people living with HIV (PLHIV), has shaped the global response to the epidemic. This paper presents qualitative findings from two large studies in eastern Africa that reveal how the advent of population-based HIV testing campaigns and efforts to accelerate antiretroviral “treatment for all” has precipitated a rapidly expanding therapeutic citizenship “project,” or social movement. The title of this paper refers to Goffman's original conceptualization of stigma as a social process through which a person's identity is rendered “spoiled.”
Keywords: HIV care cascade interventions; Spoiled identity; Redemption